Fundamentals of Wound Healing - Stallworth, Christian L. (Facial Plastic Surgery, 2021)
At the moment of soft tissue injury, an immediate wound healing ballet commences. This coordinated cascade of events works over minutes, hours, weeks, and months to restore tissue integrity and viability in an attempt to rebuild the site to its preinjured state. A thorough understanding of these processes, and options to navigate forks in the road, can help guide patient selection, surgical planning and execution, management of complications, and ultimately the restoration of tissue form and function for optimal outcomes. An exhaustive account of tissue healing mechanics is beyond the scope of this writing. However, a summation of much that is known of these processes and the directions research and therapeutic developments are currently aimed will help the facial plastic surgeon prevent or minimize debilitating functional and cosmetic consequences in the head and neck.
Keywords: wound Healing; acute; chronic wound; facial; scar